2012
DOI: 10.1259/bjr/17827549
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the ultra-high dose rate effect: implications for charged particle radiotherapy using protons and light ions

Abstract: Objective: To reinvestigate ultra-high dose rate radiation (UHDRR) radiobiology and consider potential implications for hadrontherapy. Methods: A literature search of cellular UHDRR exposures was performed. Standard oxygen diffusion equations were used to estimate the time taken to replace UHDRRrelated oxygen depletion. Dose rates from conventional and novel methods of hadrontherapy accelerators were considered, including spot scanning beam delivery, which intensifies dose rate. Results: The literature finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 37 publications
4
70
0
Order By: Relevance
“…several orders of magnitude larger than the ones used in the current therapeutic regimes [9]. While laser-driven particle beams can be thus seen as a valuable probe to investigate the core mechanisms of radiation action at the sub-nanometer and femtosecond scales [10,11], it has been suggested that the extreme spatio-temporal nature of laser-driven particle beams may ensue unknown biological responses [7,12,13]. Hence, ultra-fast high-energy particle radiobiology will have to ascertain whether and to what extent cellular radiosensitivity is influenced by such peculiar irradiation regimes.…”
Section: The Rationale For Laser-driven Cancer Hadrontherapymentioning
confidence: 99%
“…several orders of magnitude larger than the ones used in the current therapeutic regimes [9]. While laser-driven particle beams can be thus seen as a valuable probe to investigate the core mechanisms of radiation action at the sub-nanometer and femtosecond scales [10,11], it has been suggested that the extreme spatio-temporal nature of laser-driven particle beams may ensue unknown biological responses [7,12,13]. Hence, ultra-fast high-energy particle radiobiology will have to ascertain whether and to what extent cellular radiosensitivity is influenced by such peculiar irradiation regimes.…”
Section: The Rationale For Laser-driven Cancer Hadrontherapymentioning
confidence: 99%
“…The molecular effects of radiation pulses delivered to cells on these timescales are anticipated to offer new therapeutic promises. 38 Decreases in tumor radiosensitivity by transient oxygen depletion following a short-pulse irradiation 39 are an issue to be considered in high dose-rate radiation experiments. The time to reverse oxygen depletion within tumors is estimated to be> 20 s at distances of about 100 ”m from a tumor blood vessel.…”
Section: High Dose-rate Radiation Sourcesmentioning
confidence: 99%
“…The presence of oxygen is known to enhance cell lethality by a factor of about 3 for low LET radiation [106]. This enhancement is probably due to the fact that DNA radicals readily react with oxygen to generate biologically relevant DNA damage [107].…”
Section: Oxygen Effect and Dose Ratementioning
confidence: 99%
“…At ultra-high dose rates (~10 9 Gy/second or more) for low LET radiation this oxygen effect is evident in hypoxic tissue, as several Gy dose levels deplete the oxygen level at such dose rates. Although oxygen is easily accessible to single monolayer cells, oxygen recovery to regions of diffusion-related hypoxia, which are often observed in a relatively small proportion of tumor tissues, can require significant time (several seconds for tissues having distances of more than 100 ÎŒm from a tumor blood vessel) [106]. This means that the efficiency of cell inactivation in a tumor needs to be optimized or improved with the mode of irradiation featuring breaks (brief time intervals with no irradiation) of adequate duration (~seconds) such that all cells in a tissue are accessible to oxygen.…”
Section: Oxygen Effect and Dose Ratementioning
confidence: 99%